2000
DOI: 10.1097/00006842-200009000-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Wait-List Controlled Clinical Trial: The Effect of a Mindfulness Meditation-Based Stress Reduction Program on Mood and Symptoms of Stress in Cancer Outpatients

Abstract: This program was effective in decreasing mood disturbance and stress symptoms in both male and female patients with a wide variety of cancer diagnoses, stages of illness, and ages. cancer, stress, mood, intervention, mindfulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

46
612
5
25

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 886 publications
(703 citation statements)
references
References 34 publications
46
612
5
25
Order By: Relevance
“…A variety of specific mindfulness techniques were taught (e.g., attention to breathing, awareness of bodily sensations). The clinical value of this approach was supported by previous research (Speca et al, 2000), which found individual patient differences in the preference for and success with different techniques. The program instructors, two clinical psychologists and one clinical social worker, had been offering MBSR programs since 1996.…”
Section: Interventionmentioning
confidence: 54%
“…A variety of specific mindfulness techniques were taught (e.g., attention to breathing, awareness of bodily sensations). The clinical value of this approach was supported by previous research (Speca et al, 2000), which found individual patient differences in the preference for and success with different techniques. The program instructors, two clinical psychologists and one clinical social worker, had been offering MBSR programs since 1996.…”
Section: Interventionmentioning
confidence: 54%
“…Alternatively, the lack of effect also may reflect low sensitivity of the measures. For example, because both the 23 might have detected group differences in our population. Along these same lines, there also might have been a floor effect for some of these measures, because the scores were quite low at baseline and follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…In other studies that have examined the benefits of including yoga, yoga constituted only one aspect of the intervention. For example, Speca et al 23 designed an intervention that included group support and discussion, mindfulness meditation, visualization and imagery, and yoga stretches. Although they found that the participants in the intervention group experienced lower total mood disturbance and decreased overall distress, it is not clear whether the benefits were due to the yoga per se.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major limitation of that study was a small sample size (14 participants per group). More recently, Speca et al [23] demonstrated that MBSR was associated with significantly reduced mood disturbance and symptoms of stress in a heterogeneous group of cancer outpatients. The only other randomized, controlled study, published by Shapiro et al [24], involved a nonpatient population.…”
Section: Discussionmentioning
confidence: 99%